COVID‐19 plasma proteome reveals novel temporal and cell‐specific signatures for disease severity and high‐precision disease management. Issue 1 (19th December 2022) - Iosef, Cristiana; Martin, Claudio M.; Slessarev, Marat; Gillio‐Meina, Carolina; Cepinskas, Gediminas; Han, Victor K. M.; Fraser, Douglas D.
Abstract: Coronavirus disease 2019 (COVID‐19) is a systemic inflammatory condition with high mortality that may benefit from personalized medicine and high‐precision approaches. COVID‐19 patient plasma was analysed with targeted proteomics of 1161 proteins. Patients were monitored from Days 1 to 10 of their intensive care unit (ICU) stay. Age‐ and gender‐matched COVID‐19‐negative sepsis ICU patients and healthy subjects were examined as controls. Proteomic data were resolved using both cell‐specific annotation and deep‐analysis for functional enrichment. COVID‐19 caused extensive remodelling of the plasma microenvironment associated with a relative immunosuppressive milieu between ICU Days 3–7, and characterized by extensive organ damage. COVID‐19 resulted in (1) reduced antigen presentation and B/T‐cell function, (2) increased repurposed neutrophils and M1‐type macrophages, (3) relatively immature or disrupted endothelia and fibroblasts with a defined secretome, and (4) reactive myeloid lines. Extracellular matrix changes identified in COVID‐19 plasma could represent impaired immune cell homing and programmed cell death. The major functional modules disrupted in COVID‐19 were exaggerated in patients with fatal outcome. Taken together, these findings provide systems‐level insight into the mechanisms of COVID‐19 inflammation and identify potential prognostic biomarkers. Therapeutic strategies could be tailored to the immune response of severely ill patients.